Reorganizing Indigenous Peoples' Regulations to Achieve the Sustainable Development Goals - Kartiko, Nafis Dwi; Sanjaya, Niki; Indradewi, Astrid Athina; Sugianto, Fajar; Tokuyama , Shintaro (Universitas Muhammadiyah Malang, 2024)
This research examines the regulation of indigenous peoples' rights within Indonesia's national legal framework and identifies gaps between sustainable development aspirations and the implementation of existing regulations. A normative juridical method is applied to analyse legal documents, as well as assess the integration of customary law in the context of national legal pluralism. Results show that while there is constitutional recognition of indigenous peoples' rights, there are inconsistencies in actual implementation, particularly in support of sustainable economic goals. It was also found that indigenous economic development initiatives are often hampered by inadequate infrastructure and access to technology. Education relevant to indigenous needs and wider market access for indigenous products need improvement. Indigenous participation in policy formation and social protection still needs to be strengthened. In conclusion, legal reforms are needed that include improved frameworks to protect and develop the rights of indigenous peoples and ensure sustainable development goals in national development). Abstrak Penelitian ini mengkaji regulasi hak-hak masyarakat adat dalam kerangka hukum nasional Indonesia dan mengidentifikasi kesenjangan antara aspirasi pembangunan berkelanjutan dan implementasi regulasi yang ada. Metode yuridis normatif diterapkan untuk menganalisis dokumen hukum, serta menilai integrasi hukum adat dalam konteks pluralisme hukum nasional. Hasil penelitian menunjukkan bahwa meskipun ada pengakuan konstitusional atas hak-hak masyarakat adat, terdapat inkonsistensi dalam implementasi sebenarnya, terutama dalam mendukung tujuan ekonomi berkelanjutan. Ditemukan juga bahwa inisiatif pembangunan ekonomi masyarakat adat sering terhambat oleh infrastruktur yang tidak memadai dan akses terhadap teknologi yang terbatas. Pendidikan yang relevan dengan kebutuhan masyarakat adat dan akses pasar yang lebih luas untuk produk-produk adat perlu ditingkatkan. Partisipasi masyarakat adat dalam pembentukan kebijakan dan perlindungan sosial masih perlu diperkuat. Kesimpulannya, diperlukan reformasi hukum yang mencakup kerangka kerja yang lebih baik untuk melindungi dan mengembangkan hak-hak masyarakat adat serta memastikan tujuan pembangunan berkelanjutan dalam pembangunan nasional.